1997
DOI: 10.1002/(sici)1096-9853(199710)21:10<665::aid-nag896>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and volume change behaviour of soft clays: a boundary element simulation

Abstract: The relationship between the microstructure and the volume change behaviour of fine‐grained soft soils is analysed by using a model derived from the experimental observation of the microstructure of soft clays, and the Boundary Element Method (BEM). The soil is modelled as a bidimensional porous matrix containing circular pores. The matrix is linear elastic and obeys a Tresca failure criterion, and the pore size distribution follows a Gaussian normal law. The pores are randomly located, with a minimum distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A further process of crack generation is suspected to occur during oedometric compression. Based on previous results obtained in sensitive soft clays [30][31][32] in which it appeared that compression occurred by the ordered collapse of pores, starting from the largest and progressively affecting smaller and smaller pores. This mechanism was confirmed by scanning electron microscope (SEM) observations that also showed that the elastic unloading rebound was due to the local swelling of the collapsed zones.…”
Section: Discussionmentioning
confidence: 92%
“…A further process of crack generation is suspected to occur during oedometric compression. Based on previous results obtained in sensitive soft clays [30][31][32] in which it appeared that compression occurred by the ordered collapse of pores, starting from the largest and progressively affecting smaller and smaller pores. This mechanism was confirmed by scanning electron microscope (SEM) observations that also showed that the elastic unloading rebound was due to the local swelling of the collapsed zones.…”
Section: Discussionmentioning
confidence: 92%
“…For engineering analysis and design the soil mass is almost always treated as a continuum even though the soil is composed of discrete soil particles and particle groups (Mitchell & Soga, 2005). The development of the microstructure investigation of fine-grained soils started nearly five decades ago with the study of highly compressible and poorly resistant soils (Cerrolaza & Delage, 1997). From then on, many other studies and techniques on the investigation have been published and they are discussed in the following topics.…”
Section: -Microstructure Investigationmentioning
confidence: 99%